Boosting the Redox Kinetics of High‐Voltage P2‐Type Cathode by Radially Oriented {010} Exposed Nanoplates for High‐Power Sodium‐Ion Batteries. Issue 1 (29th October 2021) - Li, Feng; Fan, Ke; Hou, Peiyu; Huang, Haitao
Abstract : High‐voltage P2‐type cathode with large capacity, high air stability, and low cost has attracted extensive attention. However, large ionic radius of Na + and Na + /vacancy ordering result in low reaction kinetics and poor high‐rate capability. Herein, cobalt‐doped hierarchical structure assembled by radially oriented {010} exposed nanoplates is developed. With radially oriented grains infiltrating from surface to interior, all the {010} exposed surfaces are electrochemically active planes, and Na + ions diffuse directly into electrolyte without passing through grain boundaries, building up 3D transfer channels. The trivalent cobalt substitution suppresses unwanted Na + /vacancy ordering and increases energy barrier of the phase transition from P2‐ to O2‐type oxide. These synergetic effects remarkably boost the redox kinetics of high‐voltage P2‐type cathode. Consequently, a large reversible capacity of 112 mAh g −1 is achieved even at 20 C, indicating excellent high‐rate capability. The absence of P2–O2 phase transition also gives rise to superior cycling stability, maintaining a capacity retention of 85% after 200 cycles. In addition, full cells composed of this hierarchical P2‐type cathode and hard carbon anode deliver high energy‐ and power‐densities. These achievements offer a new insight into boosting redox kinetics of P2‐ and O3‐type layered cathodes for high‐power sodium‐ion batteries. Abstract : The cobalt‐doped hierarchical structure assembled by radially oriented {010} exposed nanoplates is proposed to boost the redox kinetics of P2‐type layered cathodes for high‐power sodium‐ion batteries.